A Cautious Approach Towards the Application of Team Misconduct - South African Commercial Catering and Allied Workers Union v Makgopela (2023) 44 ILJ 1229 (LAC) - Scelo Sibiya (Potchefstroom Electronic Law Journal)
The reality faced by the labour market is that employees are prone to committing acts of misconduct from time to time at the workplace. In case of an unexplained stock loss at the workplace however, it becomes difficult for the employer to show on a balance of probabilities that each individual employee was involved in the commission of the offence, before disciplinary action can be validly taken. Consequently, the concept of team misconduct was introduced to deal with the generic dilemma which confronts an employer who has clear evidence of stock loss but is unable to identify the perpetrators of misconduct. The evidential difficulty posed by dismissal for misconduct in circumstances where the primary misconduct has been committed by a group of employees has disseminated the concept of team misconduct.